Review an assessment of electromagnetic wave propagation in sand and dust storms at microwave and millimeter wave band- part 1 - Musa, Abdulwaheed; Nasr, Saad Osman Bashir; Hassan Abdalla Hashim, Aisha (EMW Publishing, 2014)
Electromagnetic wave propagation in arid and semi-arid regions is influenced by sand and dust storms. Meager information has hitherto been reported as to the effect of storms on telecommunication systems operating in such regions. This paper presents a survey of current understanding of the wave propagation during storms. In this first part of the review—Part I, detailed parametric assessment of some electrical and mechanical properties affecting wave propagation in sand and dust storms is given. The second part of the review—Part II describes the principle of approach and technology adopted for the investigation highlighting both strengths and drawbacks. The results demonstrate that most authors have calculated signal attenuation effect, revealing that it is not very significant unless during severe storms. A few papers indicate the possibility of more significant cross polarisation. Part I explicitly gives an account of the sand and dust storms’ phenomenon, reviews the storms’ parameters affecting electromagnetic wave propagations and discusses the microwave and millimeter wave bands.